Analysis of The Length of Stay of Premature Infants at the NICU of Hospital X in Surabaya - Sisilia Indriasari Widianingtyas; Veronica Tiwi; Cicilia Wahju Dj (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2026)
Introduction:  Premature infants with low birth weight and immature organ often require a long length of stay (LOS) at the Neonatal Intensive Care Unit (NICU), which results in increased costs, risk of infection, and burden on hospital resources. Objectives:  This study aims to analyze the length of stay of premature infants at the NICU of Hospital X in Surabaya. Methods:  An analytical observational study with a cross-sectional design. Sample: 51 premature infants treated at the NICU of Hospital X in Surabaya (total sampling). Independent variables: gestational age, birth weight, APGAR score, and nutrition; dependent variable: LOS. Analysis data use : Chi-Square and multiple logistic regression in SPSS 25. Statistical significance was considered at 0.05. Results:  The majority of infants (68.7%) had a long LOS (≥21 days). The Chi-Square test showed that gestational age (p=0.032), birth weight (p=0.018), APGAR score (p=0.044), and nutrition (p=0.021) were significantly associated with LOS. Multivariate analysis found that the dominant factor was birth weight <2500 g (OR=4.1; p=0.015), followed by gestational age <32 weeks (OR=2.6; p=0.048) and inadequate nutrition (OR=2.8; p=0.034). Conclusions:  LOS in premature infants is mainly influenced by low birth weight, low gestational age, and inadequate nutrition. Efforts to improve early nutrition, close monitoring of VLBW (Very Low Birth Weight) infants, and comprehensive clinical interventions can reduce LOS and the socioeconomic impact on families.